SELECTION FOR YIELD, ADAPTABILITY AND STABILITY OF SUGARCANE CLONES IN THREE ENVIRONMENTS OF PARANÁ STATE VIA MIXED MODELS - ZENI-NETO, Hugo; OLIVEIRA, Ricardo Augusto de; DAROS, Edelclaiton; BESPALHOK FILHO, João Carlos; ZAMBON, José Luis Camargo; IDO, Oswaldo Teruyo; WEBER, Heroldo (Scientia Agraria, 2008)
The objective of this study was to estimate genetic parameters and predict genotypic values of sugarcane clones in T3 stage in the state of Parana using the REML/BLUP methodology. This work was carried out in three environments of production in State of Paraná (Colorado, Paranavaí and Mandaguaçú), on T3 stage with 236, 243 and 202 clones, respectively, and two standard varieties. The design of the experiment was an augmented block with two repetitions and the variable evaluated was tones of brix per hectare (TBH). The clones were selected via mixed models, using the MHPRVG method (harmonic mean of the relative performance of genetic values). The most adapted, stable and productivity clones according to MHPRVG method were: RB9371, RB975245 e RB975316. The use of MHVG method (harmonic mean of genetic values) must be employed with caution in unbalanced experiments, when the tested clones are not presented in all environments.